(untitled) (Sociologisk Forskning, 2017)
Contextualizing Violence: Knowledge, gender and lines of connection in apreliminary investigation on “honour violence” I discuss some practical and theoretical problems related to the feminist project of re-contextualizing law in order to acknowledge women’s experiences. Nicola Lacey warns us that re-contextualization might result in existing misogynist presumptions being re-inscribed in “new” lines of thoughts, making the problem of gender inequality even harder to address. In this article my analytical focus is set on two cultural contexts constructed as different – a “Swedish gender equal context” and a “non-Swedish honour related context” – and the attempts made by the prosecutor and the police “to contextualize” the latter. I highlight, in the light of Lacey’s warnings, the need for a careful and grounded analysis of the issues being “contextualized” as well as a careful analysis of the norms that are supposed to guide the process of contextualization. I take my point of departure in the example of a police investigation of suspected honor related violence, committed in the context of a compulsory school.